LEVELS OF TNF-α IN ASYMPTOMATIC APICAL PERIODONTITIS - Teodora Karteva; Tatyana Todorova; Neshka Manchorova-Veleva; Maria Kazakova; Ekaterina Karteva; Donka Keskinova; Stoyan Vladimirov; Victoria Sarafian (Science & Research)

(untitled)
Introduction Asymptomatic apical periodontitis (AAP) is a chronic inflammatory process mediated by a milieu of pro-inflammatory cytokines. TNF-α is a key mediator and a potent inducer of bone resorption and connective tissue degradation. The aim of the study was to examine TNF-α production by peripheral blood mononuclear cells (PBMCs) from patients with AAP and to explore its correlation to the lesions’ characteristics. Materials and methods Patients (n=20) diagnosed with AAP were included in the study. The lesions’ characteristics were assessed with limited-volume cone beam-computed tomography (limited FOV CBCT). PBMCs were isolated from peripheral blood samples obtained from each patient. The cells were cultivated in RPMI 1640 medium and stimulated with E.coli LPS. The supernatant was collected at the 24th and 48th-hour time point. TNF-α levels were detected by ELISA. Results TNF-α concentrations decreased significantly at the 48-h time point compared to the 24-hour time point (p<0.01). Unstimulated PBMCs produced higher levels of TNF-α compared to stimulated ones. No statistically significant correlation was found between the lesions’ variables and IL-1β levels. Conclusions We suggest that TNF-α secretion is more impactful to the inflammatory process in the first 24 hours. The financial support by the National Science Fund of Bulgaria (Contract No. DM-13/2,15.12 2017) is acknowledged.